Penerapan Metode Simple Moving Average Untuk Memprediksi Hasil Laba Laundry Karpet Pada CV. Homecare - Nur Aini; Sinar Sinurat; Sumiaty Adelina Hutabarat (JURIKOM (Jurnal Riset Komputer), 2018)
CV. Homecare is a company engaged in the field of laundry carpet that serves customers in carpet washing, a business engaged in carpet laundry service for most still run the conventional system has not been using computerized data, especially in terms of predicting carpet laundry every month. Simple Moving Average is a model in making predictions. The moving average technique is used in predicting demand by calculating the average value and actual demand value of a certain number of previous periods. Each new prediction is set for a long period and used with the request of the new period, so the data on the calculation moves over time, in accordance with the name of this method. The simple moving average method is used for data that is unstable, has no trends, and does not use data weighting. With the existence of simple moving average method is one of the methods on time series prediction system model with computerized characteristics, about predicting the carpet can do apply the research technique of surgery expected carpet laundry company can do predict carpet income every month so that company can measure profit ratio which will be earned every month. So as to produce the system predicts the good results of carpet laundry results, which can be utilized and facilitate the users.